2019
DOI: 10.17305/bjbms.2019.4253
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins and inflammatory markers are useful in predicting the severity of acute pancreatitis

Abstract: Acute pancreatitis (AP) is a disease with significant morbidity and mortality. The aim of this study was to evaluate the prognostic role of inflammatory markers, particularly interleukins (ILs), in the course of AP and to determine the frequency of etiologic factors of AP. We included patients with AP who were treated at our institution from May 1, 2012 to January 31, 2015. Different laboratory parameters, including ILs, and the severity scoring systems Ranson’s criteria and Bedside Index of Severity in Acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…For example, IL6 was the key accelerator in the final differentiation of B-cells into Ig-secreting cells, and IL8 had the function on neutrophil activation [ 17 ]. IL6 and IL8 could take part in a wide variety of inflammation-associated disease by inducing the inflammatory response, such as rheumatoid arthritis [ 18 ], ulcerative colitis [ 19 ], and acute pancreatitis [ 20 ]. In acute pancreatitis, the levels of these cytokines in peripheral blood were abnormally increased and significantly associated with the disease development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL6 was the key accelerator in the final differentiation of B-cells into Ig-secreting cells, and IL8 had the function on neutrophil activation [ 17 ]. IL6 and IL8 could take part in a wide variety of inflammation-associated disease by inducing the inflammatory response, such as rheumatoid arthritis [ 18 ], ulcerative colitis [ 19 ], and acute pancreatitis [ 20 ]. In acute pancreatitis, the levels of these cytokines in peripheral blood were abnormally increased and significantly associated with the disease development.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of AP is associated with increased serum levels of inflammatory cytokines markers including TNF‐α, IL‐1β, IL‐6, IL‐8, and IL‐10 (Chen et al, 2021). Furthermore, IL‐6 is identified as a significant inflammatory cytokine marker in the development of AP (Ćeranić et al, 2020). Findings in the present study indicated that TSPAN1 silencing suppressed the cerulein‐induced hypersecretion of inflammatory cytokines such as TNF‐α and IL‐6.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, through gp130 protein, takes part in the activation of the Janus kinase/signal transducers and activators (JAK/STAT) signaling pathway [ 9 ]. The concentration of this cytokine increases earlier, and it is a more sensitive marker of severity of inflammation than C-reactive protein (CRP) [ 10 , 11 ]. The release of IL-6 from the inflamed pancreas tissue is associated with the dysfunction of this organ [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%